Efficacy of practical video demonstrations to enhance teaching and learning of psychomotor skills in a time-constrained dental prosthetic techniques course - Moses, Carmen Delicia (Stellenbosch : Stellenbosch University, 2022)
Thesis (MPhil)--Stellenbosch University, 2022.